AN ANALYSIS OF THE IMPACT OF CHANGING ACCOUNTING BASE ON AUDIT OF LOCAL GOVERNMENT OF GUNUNGKIDUL DIY - Fajrin, Farid (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2020)
The purpose of this study is to analyze the process of applying the accrual basis at the local government of Gunungkidul and its impact on the planning, implementation, and opinion of the audit as well as the cause (presence or absence) of the impact of changes in the accrual basis. This research use qualitative approach with case study research method. Data collection techniques were done through document analysis and in-depth interviews at the head of accounting division of Gunungkidul and staff, as well as The Audit Board of The Republic of Indonesia representatives of DIY. Interview data were then reduced, identified and analyzed to answer research questions. The results of this study found Changes in the accrual basis generally do not have a significant impact on planning, implementation, and audit opinions.The impact of the accrual basis is only on the understanding of the broader business processes, additional procedures for audit execution, and increased testing of controls for accounts impacted by the accrual basis.